The two-component system CpxA/CpxR is critical for full virulence in Actinobacillus pleuropneumoniae - Liu, Feng; Yao, Qing; Huang, Jing; Wan, Jiajia; Xie, Tingting; Gao, Xuejun; Sun, Diangang; Zhang, Fuxian; Bei, Weicheng; Lei, Liancheng (Frontiers in Microbiology, 2022)
Actinobacillus pleuropneumoniae, a major bacterial porcine respiratory tract pathogen causing pig pleuropneumonia, has resulted in high economic losses worldwide. The mutation of the two-component system CpxAR strongly impacted the virulence of A. pleuropneumoniae, but the underlying regulatory mechanism remained unclear. Here, we found that CpxAR positively regulated the cpxDCBA gene cluster involved in polysaccharide capsule export. A capsular layer was confirmed in wild-type cells by transmission electron microscopy, whereas cpxAR and cpxD mutants were non-capsulated. The mutants for polysaccharide capsule export gene cpxD exhibited non-capsulated and were strongly impaired in virulence for mice, indicating a major role of CPS export system in virulence. We then demonstrated that CpxR directly regulated the transcription of the CPS export gene cluster cpxDCBA. Taken together, our data suggested that CpxAR is a key modulator of capsule export that facilitates A. pleuropneumoniae survival in the host.